Visual evoked potentials in children with type 1 diabetes mellitus - Batta, Meenal; Sharma, Rajeev; Gupta, Naveenta; Garg, Sonia; Kaur, Gurmeet; Dhir, Shashi Kant; Kaur, Amarpreet (International Journal of Research in Medical Sciences, 2018)
Background: Insulin-dependent (type 1) diabetes mellitus is associated with different degrees of neuropathies affecting peripheral as well as central neural pathways. The subclinical neurological involvement in diabetic children can be assessed by changes appearing in the electrophysiological parameters like Visual Evoked Potentials (VEPs). The objective of the study was to assess the effect of type I diabetes melitus on the visual evoked potentials in children. Methods: This cross-sectional case-control study was done on 30 children with type 1 diabetes mellitus of minimum two years duration as cases and 30 age and gender matched euglycemic children with normal HbA1c taken as controls. Visual Evoked Potentials (VEPs) were done on both the groups of children and the latencies (ms) of waves -N75, P100, N145 and amplitude (μV) of wave P100 were recorded. The data was compiled in the pre-designed proforma and statistically analysed using student t-test. Results: The increase in the mean latencies of waveforms of VEPs N75, P100 and amplitude P100 were found to be highly significant statistically (p<0.001) in both the eyes among the children with type 1 diabetes mellitus. The mean latency of waveform N145 was found to be statistically insignificant in the two groups (p>0.05). Conclusions: The type 1 diabetes does affect the visual pathways in children. Visual Evoked Potentials are helpful in the detection of early changes in the conduction across the neural pathways in the sub-clinical diseases.